Evaluation of Implementation Indicators for the Family Hope Program in the Field of Education and Health in Sripendowo Village, Bandar Sribhawono District, East Lampung Regency - Apriliana Sukmawati; Ukhty Ciptawati; Heru Wahyudi (PT FORMOSA CENDEKIA GLOBAL, 2022)
To overcome the problem of poverty in Indonesia, the government has carried out various programs and incentives to overcome the problem of poverty. One of the government's special programs to accelerate poverty alleviation is the Conditional Cash Assistance Program known as the Family Hope Program (PKH). The method in this writing is descriptive qualitative. The aspect that you want to see is an evaluation of the implementation of PKH, especially in the education sector by distributing questionnaires to 62 respondents and the results obtained are that the Family Hope program in Sripendowo Village has been implemented very well. The indicators used are based on ministerial regulations in 2018